Science Communication and Education of Future Researchers. To the Question of Teaching the History and Philosophy of Science at University - L. V. Shipovalova (Высшее образование в России)
The article aims to legitimate teaching the history and philosophy of science at contemporary Russian university. It assumes to contribute to the answering the questions of what and how should future researchers and science teachers be taught. It attempts to complement the relevant researches with one aspect connected with the communication of scientists as a subject of study and education. The author argues that the theory and practice of communication can be an important element of teaching the history and philosophy of science courses for future researchers. She explains this importance by two reasons. Firstly, the communication of scientists is problematic; secondly, it can be interpreted as a condition for innovative research. The author makes a distinction between professional communication in science and science communication of scientists with other public actors. The main problem of communication between scientists is an ambiguous connection between the goals of these two types of communication. The article answers the following issues: why and how future researchers should be taught the theory and practice of these two types of communication. In the last part of the article the author analyzes the method of teaching and describes three educational strategies: historical critique, philosophical assembling and experience of dialogue. All of them can be an integral part of teaching the history and philosophy of science for future researchers.